Detection and validation of QTLs associated with seed longevity in rice (Oryza sativa L.). (27th June 2018) - Liu, Wenqiang; Pan, Xiaowu; Li, Yongchao; Duan, Yonghong; Min, Jun; Liu, Sanxiong; Sheng, Xinnian; Li, Xiaoxiang
Abstract: Seed longevity in rice is a major determinant in seed production and germplasm preservation. In this paper, a recombinant inbred line (RIL) population consisting of 172 lines derived from the cross between Xiang743 and 'Katy' was used to map quantitative trait loci (QTLs) for seed longevity (SL) after seed storage for 18 and 30 months under ambient conditions. Two putative QTLs, qSL‐2 and qSL‐8, were detected and located on chromosomes 2 and 8, respectively. qSL‐2 is an allele from Xiang743 allele and increases seed longevity. qSL‐8 was a novel QTL from 'Katy' allele and increases seed longevity. qSL‐8 explained 15.29% and 17.35% of the phenotypic variance after seed storage for 18 and 30 months, respectively. Furthermore, qSL‐8 was validated in a secondary population developed by self‐pollination of a residual heterozygous line (RHL) selected from the RIL population, which explained 25.93% of the phenotypic contribution. These results provide an opportunity for map‐based cloning of qSL‐8 . Furthermore, qSL‐8 may be a target for improving seed longevity by marker‐assisted selection (MAS) in rice.